Trends in mental health system transformation: Integrating youth services within the Canadian context. Issue 2 (March 2019) - Halsall, Tanya; Manion, Ian; Iyer, Srividya N.; Mathias, Steve; Purcell, Rosemary; Henderson, Joanna
The current mental health services system in Canada is fragmented and transitions between the youth and adult mental health systems have been identified as needing significant improvement. Integrated Youth Services (IYS) are designed to be adaptable and developmentally appropriate as well as to promote seamless transitions, including during emerging adulthood. This article provides an overview of recent developments in Canadian mental health system transformation to promote the integration of services and the holistic promotion of youth well-being. We offer an overview of the current state of knowledge related to best practices in IYS in Canada and highlight areas for future development. We also introduce Frayme, a Canadian-based international knowledge translation platform designed to connect organizations working in the youth services system to accelerate the implementation of IYS.